2011
DOI: 10.1080/08952841.2011.587732
|View full text |Cite
|
Sign up to set email alerts
|

Dating for Older Women: Experiences and Meanings of Dating in Later Life

Abstract: Research over the last 20 years has provided an increased understanding of intimate relationships in later life; however, dating in later life remains largely unexplored. The purpose of this study was to examine the meanings of dating for women in later life. In this study, dating was examined through semistructured, in-depth interviews with 14 women ages 64 to 77 who had all dated in later life. Themes that emerged from an interpretative phenomenological analysis included multiple meanings of dating in later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 10 publications
4
40
0
2
Order By: Relevance
“…Cohort differences in LAT echo earlier U.S. research on dating that found almost half of respondents aged 55 to 75 years and older described their dating relationship as “steady” and only a small number considered it a step toward marriage, leading the authors to conclude that “dating is taken seriously by older adults but not as a means to marriage,” especially by women (Bulcroft & Bulcroft, , p. 258; see also Bulcroft & O'Connor, ). Watson and Stelle () found that “young old” women did not see dating as a step toward remarrying, even in cases when dating developed into a steady, long‐term relationship; a steady, long‐term relationship, not marriage, was their goal. Older adults in the United States seriously pursue romantic partners (Stephure, Boon, MacKinnon, & Deveau, ), and, when compared with the personal ads and dating profiles of younger adults, they are less future oriented and more focused on present concerns (Alterovitz & Mendelsohn, ).…”
Section: Lat and Life Stagementioning
confidence: 99%
“…Cohort differences in LAT echo earlier U.S. research on dating that found almost half of respondents aged 55 to 75 years and older described their dating relationship as “steady” and only a small number considered it a step toward marriage, leading the authors to conclude that “dating is taken seriously by older adults but not as a means to marriage,” especially by women (Bulcroft & Bulcroft, , p. 258; see also Bulcroft & O'Connor, ). Watson and Stelle () found that “young old” women did not see dating as a step toward remarrying, even in cases when dating developed into a steady, long‐term relationship; a steady, long‐term relationship, not marriage, was their goal. Older adults in the United States seriously pursue romantic partners (Stephure, Boon, MacKinnon, & Deveau, ), and, when compared with the personal ads and dating profiles of younger adults, they are less future oriented and more focused on present concerns (Alterovitz & Mendelsohn, ).…”
Section: Lat and Life Stagementioning
confidence: 99%
“…Nearly all of the research on older daters comes from qualitative, in-depth interview studies that explore the reasons why older adults (often only women and only widows) pursue or avoid intimate relationships (Bulcroft & O’Connor, 1986; Dickson, Hughes, & Walker, 2005; McWilliams & Barrett, 2012; Stevens, 2002; Watson & Stelle, 2011). These studies illustrate the range of meanings of dating in later life.…”
mentioning
confidence: 99%
“…One study from the 1980s revealed that many daters were involved in serious, long-term relationships (Bulcroft & O’Connor, 1986). But more recent research has suggested many women view dating as a social activity that provides a unique form of companionship not achieved through friendships with other women (Davidson, 2001; Watson & Stelle, 2011). These women desired a close companion but at the same time wanted to be autonomous and ultimately were not interested in a long-term, conventional commitment (e.g., marriage or cohabitation; Dickson et al, 2005; McWilliams & Barrett, 2012).…”
mentioning
confidence: 99%
“…From a theoretical standpoint, many older adults choose to cohabit precisely because the expectations for care are weaker. Cohabitation does not require taking a vow to care for a partner “in sickness and in health.” Women especially favor cohabitation over remarriage because it is a pathway that allows them to avoid the traditional gendered expectations that accompany marriage (Talbott, 1998; Watson & Stelle, 2011). Older unmarried women are often widows who have cared for a former spouse.…”
Section: Family Policymentioning
confidence: 99%